The effect of microstructure heterogeneity on the microscale deformation of ultrafine-grained aluminum - Kammers, Adam D.; Wongsa-Ngam, Jittraporn; Langdon, Terence G.; Daly, Samantha (My University, 2014)
A combined approach of scanning electron microscopy and digital image correlation was used to examine microstructure-scale strain localization and active deformation mechanisms in ultrafine-grained (UFG) high purity (99.99%) aluminum processed by equal-channel angular pressing (ECAP). The results from tensile tests demonstrate a strong relationship between the heterogeneous microstructure and strain localization. The localized deformation was investigated in areas that contain significantly different microstructural features typical of ECAP processed aluminum. It was found that areas of the UFG microstructure containing primarily low angle grain boundaries deformed by dislocation slip and behaved similarly to a coarse-grained material. The greatest strain localization occurred at high angle grain boundaries (HAGBs) separating distinct microstructure regions and with median surface trace angles of approximately 26.6°. In areas of banded microstructure, shear strain localization as high as 30% and shear displacements of up to 500 nm occurred at the HAGBs separating bands, suggesting grain boundary sliding. Copyright © 2014 Materials Research Society.
Keywords: Metal; nanostructure; scanning electron microscopy (SEM)